2006
DOI: 10.2514/1.12697
|View full text |Cite
|
Sign up to set email alerts
|

Low Vulnerable Sheet Explosive Based on 3-Nitro-1,2,4-triazol-5-one

Abstract: Nitrotriazolone incorporated sheet explosives were prepared and evaluated with respect to their explosive characteristics as well as mechanical and thermal behavior. 1,3,5-Trinitro-1,3,5-triaza-cyclohexane (RDX)/Estane (85:15) composition (density, 1:23 g=cm 3 and tensile strength, 0.5 MPa) was taken as reference and the effect of replacement of RDX by nitrotriazolone to the extent of 5-25% was studied. Inclusion of nitrotriazolone led to a remarkable increase in density (1:23 ! 1:41 g=cm 3 ) and mechanical pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 10 publications
(10 reference statements)
0
12
0
Order By: Relevance
“…A cylindrical pressed RDX:Wax (95:5) donor charge of diameter 30 mm and height 100 mm, having a density of 1640 kg/m 3 and VOD of 8100 m/s, was used to generate the shock wave. The wave was allowed to pass through an aluminium block of diameter 63 mm of density 2700 kg/m 3 , with the height being varied from 31 mm to 60 mm.…”
Section: Characterization Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A cylindrical pressed RDX:Wax (95:5) donor charge of diameter 30 mm and height 100 mm, having a density of 1640 kg/m 3 and VOD of 8100 m/s, was used to generate the shock wave. The wave was allowed to pass through an aluminium block of diameter 63 mm of density 2700 kg/m 3 , with the height being varied from 31 mm to 60 mm.…”
Section: Characterization Methodsmentioning
confidence: 99%
“…Nath et al [2] and Mukundan et al [3] have reported RDX as a major energetic ingredient in sheet explosive formulations with ethylene vinyl acetate (EVA) and Estane binder systems. These formulations were prepared by a rolling process.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…
Abstract:The present investigation reports the use of 2, 4,6,8,10,4,6,8,10, in sheet explosive formulations. In this study, hydroxyl terminated polybutadiene (HTPB) based sheet explosives were prepared incorporating the powerful explosive CL-20 as a partial replacement for hexahydro-1,3,5-trinitro-1,3,5-triazine(RDX).
…”
mentioning
confidence: 99%
“…RDX-based sheet explosive formulations with various binders like natural rubber and thermoplastic elastomers (TPEs) such as copolymers of ethylene and vinyl acetate [ethylene vinyl acetate (EVA) copolymers] and Estane have been studied [5][6] . These formulations were prepared by rolling process.…”
Section: Introductionmentioning
confidence: 99%